Role and mechanism of neural stem cells of the subventricular zone in glioblastoma - Zhang, Gui-Long (World J Stem Cells, 2021)
Glioblastoma multiforme (GBM), the most frequently occurring malignant brain tumor in adults, remains mostly untreatable. Because of the heterogeneity of invasive gliomas and drug resistance associated with the tumor microenvironment, the prognosis is poor, and the survival rate of patients is low. Communication between GBMs and non-glioma cells in the tumor microenvironment plays a vital role in tumor growth and recurrence. Emerging data have suggested that neural stem cells (NSCs) in the subventricular zone (SVZ) are the cells-of-origin of gliomas, and SVZ NSC involvement is associated with the progression and recurrence of GBM. This review highlights the interaction between SVZ NSCs and gliomas, summarizes current findings on the crosstalk between gliomas and other non-glioma cells, and describes the links between SVZ NSCs and gliomas. We also discuss the role and mechanism of SVZ NSCs in glioblastoma, as well as the interventions targeting the SVZ and their therapeutic implications in glioblastoma. Taken together, understanding the biological mechanism of glioma-NSC interactions can lead to new therapeutic strategies for GBM.